Carbon Chain Rupture: Base-Induced Radical C–C Bond Cleavage of Alkylbenzimidazoles - Fu, Xuegang; Guo, Dongyang; Yan, Yuting; Marselo, Timotius; Zhang, Mingyu; Zhang, Zhenghan; Li, Siying; Huang, Jianhui (Synthesis, 2022)
A base-mediated aerobic oxidation of alkylbenzimidazoles for the preparation of carboxylic acids is described. A number of aliphatic carboxylic acids have been prepared in good to excellent yields via a C–C bond rupture process. Preliminary mechanistic studies suggest the reaction undergoes a radical pathway initiated by strong bases such as potassium amide. This type of transformation provides an alternative strategy for the access of important carboxylic acid moieties.
Keywords: C–C cleavage; radical generation; heterocycles; potassium hexamethyldisilazide; aerobic oxidation